Rebuilding a repertoire; reconstitution of γδ T cells after allogeneic stem cell transplantation - Janssen, Anke (Utrecht University, 2024)
γδ T cells are among the first immune cells to recover after allogeneic stem cell transplantation (SCT). SCT still remains the only curative treatment for various hematological malignancies, but is often complicated by infections, relapses and graft versus host disease (GVHD). T cells play a crucial role in in both the desired graft versus leukemia effect and severe complications such as GVHD. Whereas αβ T cells are extensively studied after SCT, the role of γδ T cells is less clear. In this thesis the role of γδ T cells after SCT is explored and their potential for therapeutic interventions is investigated. We showed a favorable outcome with less GVHD after αβ T cell depleted SCT in a multicenter prospective phase 1/2 clinical study. In depth analyses of the immune system after αβ T cell depleted SCT in the context of viral reactivations such as CVM and EBV showed the differences in reconstitution of the αβ- and γδ T cells. In the abcense of sufficient numbers and diversity of αβ T cells, γδ T cells played a crucial role in the first months after SCT as was suggested by focussing of the γδ T cell receptor repertoire. In the second part of this thesis we identified novel tumor reactive γδ T cell receptors against a variety of cancer types. These receptors are tested in the TEG format (αβ T cells engineered to express a defined γδTCR) and will be leads for future γδ T cell based immune effector cell therapies.
Keywords: stem cell transplantation; immune reconstitution; γδ T cells; αβ T cells; immune effector cells; T cell receptor repertoire; T cell receptor sequencing; CMV; EBV; GVHD